Akuntabilitas Kinerja dalam Bingkai Tauhid Sosial: Suatu Refleksi Teologi Al Ma’Un - Wa Ode Rayyani; Ahmad Abbas (Jayapangus Press, 2020)
The study of this research aims to comprehend the concept and meaning of the accountability of social performance in Muhammadiyah University of Makassar. This study is qualitative using interpretive paradigm through etnomethodology approach. This study finds that Al Ma’un teology in Muhammadiyah University of Makassar is termed in the form of the servitude to God. In the university, a lot of products are the manifestation of accountability of social performance providing fundamental values including ukhuwah and sincerity in conducting the performance program, profesionalism, and independency.